Synthesis of new biologically active compounds based on 6-methyluracil-5-sulfochloride and alkylamines - Abdo-Allah, Masud; Shypidchenko, Maryna; Kulyhina, Zoia; Isak, Alexandr; Popov, Yevgeniy (Technology audit and production reserves, 2018)
The object of research is 6-methyluracil-5-sulfochloride (MUSCH) and syntheses based on it mono- and disubstituted sulfonamides. A number of new compounds have been synthesized, which are not described in the literature, therefore, it is possible that among the synthesized compounds there are also such compounds that will exhibit, to varying degrees, biological activity. There were two problems that were solved during the research. The first problem relates to the fact that most of the previous works were characterized by a low yield of methyluracil sulfochloride and this inhibited its wide application in organic synthesis. By selecting the appropriate synthesis conditions, that is, by reacting the reaction of methyluracil with chlorosulfonic acid in an inert organic solvent (dichloroethane, carbon tetrachloride, chloroform), it was possible to obtain methyluracil sulfon chloride in excess of 96 %. Another problematic area was the interaction of MUSCH with amines. It turned out that in order to increase the yield of the reaction product, synthesis is conveniently carried out in a medium of inert organic solvents (dioxane, dimethylformamide, dimethylsulfoxide) in the presence of bases (soda, potash, sodium acetate). Good results were obtained by carrying out the reaction in pyridine, which simultaneously serves as a solvent and a base. Physical and chemical analysis methods (IR and NMR spectroscopy) as well as elemental composition data were used to confirm the structure and composition of the compounds obtained. A number of new sulfonamides, not described in the literature, have been obtained. This is due to the fact that the proposed method has a number of features, in particular, a new method of introducing a sulfochloride group into aromatic compounds has been proposed. Thanks to this, it is possible to obtain new organic preparations that can be used in a variety of industries. In comparison with similar known methods, this provides such advantages as an increase in the yield of the final reaction products, their purity and individuality, and the availability of the synthesis method.